“thi all vores lærdom er dog mesten halfverk og stumpeviis”: en islandsk litteraturhistorie fra det 18. århundrede - Ingólfsdóttir, Guðrún; Sigurðardóttir, Þórunn (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2015)
Apparatus Literariam Islandicam: An Icelandic History of Literature from the Eighteenth CenturyThis article discusses an Icelandic literary history, compiled in the first half of the eighteenth century. The author was Jón Ólafsson from Grunnavík, who is best known for his work at the Arnamagneana collection in Copenhagen. In the seventeenth and eighteenth centuries, European intellectuals began to write literary histories where literature was classified and defined in a novel manner, and which included precise information on various authors and their literary products. Jón Ólafsson’s history is a part of this effort. In his work, he deals with Icelandic poets and literati from the Middle Ages to his own time. The work demonstrates many of the main characteristics of literary histories of this period. The author borrows, for example, the methods of the Danish literary historian Albert Thura, but he is also influenced by Icelandic intellectuals such as Árni Magnússon, Þormóður Torfason and Páll Vídalín. Jón Ólafsson’s narrative style is, however, rather peculiar and his text is partly based on Icelandic oral tradition. An interesting part of Jón Ólafsson’s work is a chapter on female intellectuals and poets, but there he follows Thura’s example. Jón Ólafsson’s history has never been printed; neither has it been widely used by scholars. The authors of this article are preparing an edition of the work.
Keywords: Icelandic literary history; Jón Ólafsson from Grunnavík; literary sources; literary women